PENGARUH METODE RESITASI DALAM PEMBELAJARAN SOSIOLOGI TERHADAP HASIL BELAJAR SISWA DI KELAS X SMA NEGERI 1 PANCUNG SOAL KABUPATEN PESISIR SELATAN - Fitri, Meliya - (Pendidikan Sosiologi, 2014)
This research is motivated by the low learning outcomes Sociology Students of class X SMA N 1 beheaded Problem academic year 2013/2014. This is due to the many students dont pay attention to the learning activities when teachers explain the learning materials. The problem in this study is "How do the recitation method in teaching Sociology of the results of class X student of SMA N 1 beheaded problem". This study aimed to describe the method of recitation influence on learning outcomes of students in SMAN 1 Problem beheaded. This type of research experiments. The instrument used is a matter of being tested at the end of the study. Differences in learning outcomes between the experimental class and the control class used test techniques Z. Based on the analysis of data obtained by the average value of the experimental class average of 71.21 and 38.19 control class. Hypothesis testing used the Z test using SPSS version 15.0, the value of Z count is greater than the price of 12.005 tables 2.056 Z which means the hypothesis is accepted at the significance level Î± = 0.05. It can be concluded that there is an influence in the recitation method of teaching sociology student learning outcomes in class X SMA Negeri 1 Problem beheaded.